2000
DOI: 10.1128/iai.68.3.1457-1464.2000
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial Development Is Adversely Affected by Minor Changes in Amino Acid Supply, Blood Plasma Amino Acid Levels, and Glucose Deprivation

Abstract: This study has demonstrated the extreme sensitivity of Chlamydia trachomatis growing in McCoy cells to small changes in external amino acid supply. In the absence of cycloheximide, a decrease in the amino acid concentration of medium to 75% of control values was sufficient to induce the growth of enlarged chlamydial forms of reduced infectivity. Morphology became more distorted and the yield of infectious particles from inclusions declined as medium amino acid levels were further reduced. These events correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 46 publications
4
63
0
Order By: Relevance
“…This is the prime source of carbon and energy for Chlamydiaceae (60), which lack the ability to import glucose and which further lack hexokinase. It is of interest in this context that persistence can be triggered by manipulation of glucose availability to host cells in a tissue culture system (46).…”
Section: Impact Of Trp Limitation On Carbon Sourcementioning
confidence: 99%
“…This is the prime source of carbon and energy for Chlamydiaceae (60), which lack the ability to import glucose and which further lack hexokinase. It is of interest in this context that persistence can be triggered by manipulation of glucose availability to host cells in a tissue culture system (46).…”
Section: Impact Of Trp Limitation On Carbon Sourcementioning
confidence: 99%
“…Global deprivation of amino acids and other nutrients, especially iron and glucose, can also cause developing chlamydiae to enter persistence (Harper et al, 2000;Raulston, 1997). To investigate the possibility that HSV-2 co-infection induces chlamydial persistence by limiting iron availability, we first determined whether co-infected cells were iron-deprived.…”
Section: Hsv-2 Induction Of Chlamydial Persistence Is Not Mediated Bymentioning
confidence: 99%
“…Interestingly, persistent chlamydiae can re-enter the normal developmental cycle and recover infectivity if the environmental stressor is removed. For example, nutrient-deprived, persistent chlamydiae resume development into infectious EBs if the appropriate nutrients are replenished (Harper et al, 2000;Matsushima et al, 1999;Raulston, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Research from multiple teams has demonstrated that an encounter with specific stimuli can transform Chlamydia into a third state called 'persistence' (Clark et al, 1982;Harper et al, 2000), which has been defined as a reversible interruption of productive intracellular chlamydial growth mediated by environmental factors (Beatty et al, 1994). Persistence is an alternative outcome of a productive bacterial infection where a subpopulation of the bacteria becomes 'invisible' in response to prolonged antibiotic treatment, warding off innate and adaptive immune responses, causing little or no symptoms in the infected host, and possibly unnoticed by the diagnostician (Bavoil et al, 2000).…”
Section: Introductionmentioning
confidence: 99%